2022
DOI: 10.1155/2022/7509532
|View full text |Cite|
|
Sign up to set email alerts
|

Application Based on Artificial Intelligence in Substation Operation and Maintenance Management

Abstract: To fulfill state grid Industry’s demands for smart and digitized business growth, traditional technological approaches have fallen short. Artificial intelligence (AI) technology enables coming up with solutions because electricity business types and volumes are constantly expanding and developing. Intelligent automation was a part of China’s smart grid development from the outset, and it continues to grow in the country’s electricity system. Smart substation operations and maintenance could benefit from the us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…After the SVM training is completed, use the trained plane to test the two types of data obtained by K-means clustering, and use the data predicted by the SVM to retrain the SVM segmentation plane, and iteratively update the SVM segmentation plane in this way until the SVM is used to predict the data. Until the number of errors no longer changes 4 , after a sequence of computations and optimizations, the ultimate outcome is the attainment of the maximum interval hyperplane. The procedural details of this approach are visually depicted in Figure 2, presenting the flow chart that outlines the step-by-step progression of the method.…”
Section: Kmeans-svm Model Data Anomaly Detection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the SVM training is completed, use the trained plane to test the two types of data obtained by K-means clustering, and use the data predicted by the SVM to retrain the SVM segmentation plane, and iteratively update the SVM segmentation plane in this way until the SVM is used to predict the data. Until the number of errors no longer changes 4 , after a sequence of computations and optimizations, the ultimate outcome is the attainment of the maximum interval hyperplane. The procedural details of this approach are visually depicted in Figure 2, presenting the flow chart that outlines the step-by-step progression of the method.…”
Section: Kmeans-svm Model Data Anomaly Detection Methodsmentioning
confidence: 99%
“…Finally, the dual problem is solved to obtain the solution of the original problem, and the maximum margin hyperplane is obtained. Then input data into the established model to judge whether the data is abnormal data 14 . Figure 1 displays the outcomes attained through the utilization of support vector machines for classification purposes.…”
Section: Kmeans-svm Model Establishmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%